Malignant Perivascular Epithelioid Cell Tumor of Ovary: A Rare Case Report - Anuradha Sharma; Reetika Sharma; Jyoti Bala; Monika Sharma (Journal of Mid-Life Health)
Perivascular epithelioid cell tumors (PEComas) have unique morphology comprised perivascular epitheloid cells and express both melanocytic and smooth muscle cell markers. Gynecological PEComas account for approximately 25% of all PEComas, and in most cases, the primary site of the tumor is the uterine body. Ovarian PEComa is exceptional. Here, we report a case of primary malignant PEComa of ovary in a 38 years female.